1997
DOI: 10.1046/j.1365-2796.1997.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐oestrogen tamoxifen produces haemodilution in normal postmenopausal women

Abstract: Abstract. Grey AB, Evans MC, Kyle C, Reid, IR (University of Auckland, Auckland, New Zealand). The anti-oestrogen tamoxifen produces haemodilution in normal postmenopausal women. J Intern Med 1997; 242: 383-8. Objectives.To report the effects of the anti-oestrogen tamoxifen on biochemical and haematological parameters. Design. Randomized, double-blind comparison of tamoxifen 20 mg per day and placebo, over two years. Setting. A university hospital. Subjects. Forty-six healthy late-postmenopausal women (mean, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Despite this improvement, T0 values were not reached, contrary to what occurred in the case study of Savage, Dittus and Lakoski (25), in which the athlete recovered her initial hemoglobin levels after the end of treatment. Our results agree with those reported by Grey et al (26), who showed in their research that women with BC treated with ET suffered hemodilution, presenting significantly lower erythrocyte and hemoglobin values than the control group. The fact that our athlete was still in treatment with ET could explain the results at a hematological level.…”
Section: Comentado [Tpb4r3]supporting
confidence: 93%
“…Despite this improvement, T0 values were not reached, contrary to what occurred in the case study of Savage, Dittus and Lakoski (25), in which the athlete recovered her initial hemoglobin levels after the end of treatment. Our results agree with those reported by Grey et al (26), who showed in their research that women with BC treated with ET suffered hemodilution, presenting significantly lower erythrocyte and hemoglobin values than the control group. The fact that our athlete was still in treatment with ET could explain the results at a hematological level.…”
Section: Comentado [Tpb4r3]supporting
confidence: 93%
“…Grey et al [12] reported the effects of tmx on biochemical and hematological parameters. They found decline of Hb, Hct, RBC, and WBC count after tmx treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In other hand, tamoxifen treatment revealed a drop in hematological values after 2 and 4 weeks of administration. Similarly, (Grey et al, 1997) who found a decline in Hemoglobin (Hb), hematocrit (HCT), red blood cell count (RBCs), and WBC count after tamoxifen treatment. Mannucci et al (1996) evaluated hemostatic factors in tamoxifen use; they showed that Hct, Hb, and platelet levels fell in the group treated with tamoxifen.…”
Section: Discussionmentioning
confidence: 96%